2013
DOI: 10.1111/jocn.12413
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cold pack on labour pain relief and birth outcomes: a randomised controlled trial

Abstract: Local cold therapy could be included in labour pain management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 38 publications
2
18
0
6
Order By: Relevance
“…The decrease in pain was higher in the ice application group. Furthermore, the current finding is in harmony with the study of Shirvani & Ganji (2014) [32] who had conducted a randomized controlled trial about the influence of cold pack on labour pain relief and birth outcomes in Iran. They reported that labor pain intensity using VAS was significantly lower in cold therapy group compared with control.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The decrease in pain was higher in the ice application group. Furthermore, the current finding is in harmony with the study of Shirvani & Ganji (2014) [32] who had conducted a randomized controlled trial about the influence of cold pack on labour pain relief and birth outcomes in Iran. They reported that labor pain intensity using VAS was significantly lower in cold therapy group compared with control.…”
Section: Discussionsupporting
confidence: 63%
“…[37] The current finding is relatively in accordance with two studies. First the pervious mentioned study done by Shirvani et al (2013), [32] which reported that maternal satisfactory rate was higher in cold therapy group compared to control group. Second, Abdel Ghani (2014) [38] who did study about effect of heat and cold therapy during the first stage of labor on women perception of birth experience in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…Also, more reduction of pain was observed at the first phase during 5 -6 cm, 7 -8 cm, and 9 -10 cm dilata-tions in the heat therapy group compared with the control group. Most studies did not compare the relieving effect of heat and cold (23). In the current study, the heat therapy intervention was also conducted at the second phase of labor, which also showed the reduction of pain at the second phase in heat therapy group.…”
Section: Discussionmentioning
confidence: 72%
“…Results showed that the severity of pain was reduced in the first phase of labor during 5 -6 cm, 7 -8 cm, and 9 -10 cm dilatations as well as the second phase, and this pain reduction was statistically significant compared with that of the control group (7). In the current study, although the method of intervention was not frequently repeated and the effects of cold and heat therapy were examined separately, the obtained results regarding the reduction of pain severity at the first phase during 5 -6 cm, 7 -8 cm, and 9 -10 cm dilatations as well as the second phase of labor were consistent with the findings of Ganji et al Furthermore, results of the study by Shirvani et al, that investigated the effect of ice pack on pain reduction and labor outcomes showed that using ice pack on abdomen and back for 10 minutes every 30 minutes at the first phase and also on perineum for five minutes every 15 minutes at the second phase of labor could not significantly reduce the pain severity at the first phase during 5 -6 cm, 7 -8 cm, and 9 -10 cm dilatations as well as the second phase of labor (23). In their study, although pain intensity was slightly lower in the heat therapy group during labor, it was not significantly different among the three groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation